Equine Herpesvirus Protein E10 Induces Membrane Recruitment and Phosphorylation of Its Cellular Homologue, Bcl-10 - Thome, Margot (The Rockefeller University Press, 2001)
v-E10, a caspase recruitment domain (CARD)-containing gene product of equine herpesvirus 2, is the viral homologue of the bcl-10 protein whose gene was found to be translocated in mucosa-associated lymphoid tissue (MALT) lymphomas. v-E10 efficiently activates the c-jun NH(2)-terminal kinase (JNK), p38 stress kinase, and the nuclear factor (NF)-κB transcriptional pathway and interacts with its cellular homologue, bcl-10, via a CARD-mediated interaction. Here we demonstrate that v-E10 contains a COOH-terminal geranylgeranylation consensus site which is responsible for its plasma membrane localization. Expression of v-E10 induces hyperphosphorylation and redistribution of bcl-10 from the cytoplasm to the plasma membrane, a process which is dependent on the intactness of the v-E10 CARD motif. Both membrane localization and a functional CARD motif are important for v-E10–mediated NF-κB induction, but not for JNK activation, which instead requires a functional v-E10 binding site for tumor necrosis factor receptor–associated factor (TRAF)6. Moreover, v-E10–induced NF-κB activation is inhibited by a dominant negative version of the bcl-10 binding protein TRAF1, suggesting that v-E10–induced membrane recruitment of cellular bcl-10 induces constitutive TRAF-mediated NF-κB activation.